Prototype of Fire Fighting Robot (International Journal of Scientific Research in Science and Technology, 2024)
Firefighting is as one of the most precarious job in the world. Thousands of firefighters lose their lives every year trying to save others. During some critical situations when there is a possibility of structural collapse, a hard decision has to be made to not go inside and do damage control from the outside which further leads to more casualties. Fire Fighting is one of the least automated field of work. Most of the jobs in firefighting are done manually. In recent years, proliferation of firefighting incidents has underscored the needs for automation in fire fighting to make it more efficient, reliable and save human lives. This paper presents the design development and implementation of an Autonomous firefighting robot equipped with audrino uno microcontroller and flame sensors. The robot utilises Audrino uno microcontroller for its ease for its computational capabilities and programming while the flame sensors provide real-time information about the fire. The Autonomous function capability is achieved through a combination of sensor data processing and decision making algorithms. The effectiveness of the system is determined through experimental evaluation.